1999
DOI: 10.1021/jo990805t
|View full text |Cite
|
Sign up to set email alerts
|

Palladium/P,O-Ligand-Catalyzed Suzuki Cross-Coupling Reactions of Arylboronic Acids and Aryl Chlorides. Isolation and Structural Characterization of (P,O)-Pd(dba) Complex

Abstract: The phenyl backbone-derived P,O-ligands 1 and 2 were investigated for their utility as ligands in palladium/ligand-catalyzed Suzuki reactions. The 2-(2'-dicyclohexylphosphinophenyl)-2-methyl-1,3-dioxolane (ligand 1) in combination with Pd(dba)(2) affords an efficient catalyst for general Suzuki reactions of a wide variety of arylboronic acids and aryl chlorides, bromides, and iodides to afford the desired biaryl products in high isolated yields. Arylboronic acids and aryl chlorides containing electron-poor, el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
78
0
3

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 200 publications
(84 citation statements)
references
References 22 publications
3
78
0
3
Order By: Relevance
“…Guram and co-workers have shown that a combination of the phenyl backbone-derived P -O ligand 24 and Pd(dba) 2 gives an efficient catalyst system for the SM cross-coupling of a variety of aryl chlorides and arylboronic acids using CsF/dioxane/100 -1108C conditions. 41 This efficient catalytic system has also permitted o-substitution on one or both coupling partners and electron-rich and EWGs were tolerated. 42 The use of the catalytic cross-coupling reaction for the preparation of aryl-functionalised heterocycles with multiple applications is increasing at an accelerating phase.…”
Section: Sm Coupling Reactions With Aryl Chloridesmentioning
confidence: 99%
“…Guram and co-workers have shown that a combination of the phenyl backbone-derived P -O ligand 24 and Pd(dba) 2 gives an efficient catalyst system for the SM cross-coupling of a variety of aryl chlorides and arylboronic acids using CsF/dioxane/100 -1108C conditions. 41 This efficient catalytic system has also permitted o-substitution on one or both coupling partners and electron-rich and EWGs were tolerated. 42 The use of the catalytic cross-coupling reaction for the preparation of aryl-functionalised heterocycles with multiple applications is increasing at an accelerating phase.…”
Section: Sm Coupling Reactions With Aryl Chloridesmentioning
confidence: 99%
“…In the corresponding reports, the efficiency was assigned to the ability of such phosphines to form P,O-chelated monophosphine intermediates. [37] According to more recent investigations on Suzuki crosscoupling reactions, the formation of a Pd(0)-monophosphine complex appears to be a key step that precedes the oxidative addition step of aryl bromides. [38][39][40][41][42] On the other hand, the transient binding of an oxygen atom is expected to increase the electronic density of the metal centre, thereby favouring the oxidation addition step, irrespective of whether the active species is a bis-or a mono-phosphine complex.…”
Section: ·Hmentioning
confidence: 99%
“…Iit has been shown that a catalytic system comprising Pd 2 (dba) 3 and semi-labile aminophosphines exhibited superior catalytic activity in C-C coupling reactions compared to those using traditional phosphines [16][17][18][19]. In particular, functionalized aminophosphines can significantly alter the properties of the transition-metal complex [3], thereby providing a strategy to enhance the activity of such catalytic systems [4].…”
Section: Introductionmentioning
confidence: 99%